2019
DOI: 10.1097/pcc.0000000000001781
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Ventilation During Pediatric and Neonatal Critical Care Transport: A Systematic Review*

Abstract: Objectives: Noninvasive ventilation is increasingly used in neonatal and pediatric patients, but the intensive care transport setting is lagging in terms of availability of noninvasive ventilation for children. The objective of this systematic review of the literature was to answer the question: In children 0 days to 18 years old, who are hospitalized with acute respiratory distress and require critical care transport, is noninvasive ventilation effective and safe during transport? … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 29 publications
1
22
0
1
Order By: Relevance
“…25 A summary of previous research evaluating the use of NIV and HFNCT during paediatric transport is presented in Table 2. [32][33][34][35][36][37][38] Unfortunately, all of the studies evaluating NIV and HFNCT outcomes during transport were observational in nature. Therefore, there is a need for RCTs comparing outcomes with HFNCT to those of CPAP and other modes of NIV during paediatric and neonatal transport.…”
Section: Application Outside Of Paediatric Intensive Carementioning
confidence: 99%
See 4 more Smart Citations
“…25 A summary of previous research evaluating the use of NIV and HFNCT during paediatric transport is presented in Table 2. [32][33][34][35][36][37][38] Unfortunately, all of the studies evaluating NIV and HFNCT outcomes during transport were observational in nature. Therefore, there is a need for RCTs comparing outcomes with HFNCT to those of CPAP and other modes of NIV during paediatric and neonatal transport.…”
Section: Application Outside Of Paediatric Intensive Carementioning
confidence: 99%
“…Franklin et al 24 Boyle et al concluded that HFNCT was a safe option for transporting neonates, provided that the neonate was stable for 24 hours pre-transfer and certain pre-requisites were met concerning age, weight and flow at the time of transfer. 39 Moreover, the researchers noted that HFNCT usage was associated Table 2: Summary of selected research evaluating the use of noninvasive ventilation and high-flow nasal cannulae therapy during paediatric transport [32][33][34][35][36][37][38] Author and year of study Study design…”
Section: Study Setting Sample Outcomementioning
confidence: 99%
See 3 more Smart Citations